Abnormal Dexamethasone Suppression Tests in a Rifapentine-Treated Patient With Primary Aldosteronism - Wang, Hongman; Song, Ying; Xu, Zhixin; Jing, Ying; He, Wenwen; Feng, Zhengping; Li, Qifu; Yang, Shumin (Frontiers in Endocrinology, 2020)
Aldosterone producing adenomas (APA) is one of the main causes of primary aldosteronism (PA). Because a large benign-appearing unilateral masse (>1cm in diameter) may represent an aldosterone and cortisol co-secreting adenoma, and dexamethasone suppression testing is required in these patients to exclude or confirm the diagnosis of hypercortisolism. Tuberculosis is highly prevalent in China, and rifamycins are often used in these patients. Rifapentine belonging to the rifamycin family, and we herein for the first time report a case of misdiagnosis with hypercortisolism due to rifapentine in a patient with APA. Therefore, in patients treated with rifapentine, diagnosis of hypercortisolism should be prudent as the results of dexamethasone suppression tests can be very misleading.